STUDENTS’ MATHEMATICAL CONNECTION ABILITY IN TERMS OF SELF-CONFIDENCE - Anisa Hilmia Risdayati; Erdawati Nurdin; Annisah Kurniati (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
The connection was needed to solve mathematics problems. In connecting some concepts existing in mathematics to other fields of science, student self-confidence was required to solve the encountered problems. It was qualitative research, and this research aimed at knowing and describing students’ mathematical connection ability derived from their self-confidence in quadrilateral and triangle materials. The subjects of this research were the seventh-grade students at Junior High School of Juara Pekanbaru. The purposive sampling technique was used in this research. The instruments used in this research were the self-confidence questionnaire, mathematical connection ability test question, and interview guideline. All data were analyzed in three steps—data reduction, data display, and concluding. The research findings and data analyses showed that students’ self-confidence at Junior High School of Juara Pekanbaru differed. Overall, student mathematical connection ability was in enough category with 71.7%. Students with high self-confidence owned very good mathematical connection ability category, students with moderate self-confidence owned enough mathematical connection ability category, and students with low self-confidence owned very poor mathematical connection ability category.